Sports participation and psychosocial health: a longitudinal observational study in children - Janet Moeijes; Jooske T. van Busschbach; Ruud J. Bosscher; Jos W. R. Twisk (BMC, 2018)
Abstract Background It is well known that sports participation is positively associated with psychosocial health in children, but details about this association over time are lacking. This study aimed to explore longitudinal associations between several characteristics of sports participation and three aspects of psychosocial health (internalizing problems, externalizing problems and prosocial behaviour) in Dutch children aged 10-12 years. Methods Data from 695 fourth-grade primary school children were included at baseline; 10-13 months later, 487 children (response rate 70.1%) were retained. At both time points, children reported on their sports participation (Move and Sports Monitor Questionnaire - Youth Aged 8-12 Years) and psychosocial health (Strength and Difficulties Questionnaire). Longitudinal associations between several characteristics of sports participation and the three aspects of psychosocial health were analysed using linear mixed models, both clustering the repeated measures within children and clustering the children within schools. In addition to crude analyses, analyses were performed adjusting for sex, age, BMI, household composition, SES and frequency of sports participation. Results Membership in a sports club, moderate or high frequency of sports participation, performing team sports, performing outdoor sports, performing contact sports and involvement in competition were longitudinally associated with fewer internalizing problems. The longitudinal association of higher frequency of sports participation with fewer internalizing problems was stronger as a child's BMI increased. The association of performing team sports with fewer internalizing problems was only observed for boys. Membership in a sports club and moderate or high frequency of sports participation were also longitudinally associated with better prosocial behaviour. These associations with prosocial behaviour were stronger for girls. None of the characteristics of sports participation examined were longitudinally associated with externalizing problems. Conclusions This study shows that from a longitudinal perspective, fewer internalizing problems and better prosocial behaviour were seen in children who were active in sports. Fewer internalizing problems were also associated with the kind of sports participation; for example, with performing outdoor sports. No associations were found for externalizing problems. Future research should preferably take the form of an intervention to investigate whether the observed statistical associations are of a causal nature.